Needs Analysis of Paragraph Writing Materials Using The Flipped Classroom Model for EFL Students at MTsN 1 Kota Bengkulu - Reci Rinjani Fahlepi; Fera Zasrianita; Andriadi Andriadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines students’ needs in learning paragraph writing and the role of the Flipped Classroom model in supporting this process. A mixed-method approach was used, involving questionnaires and classroom observations with students of MTsN 1 Kota Bengkulu. The findings show that students still face difficulties in developing ideas and organizing sentences into coherent paragraphs, despite having prior experience in writing. The results also indicate a very strong need for structured materials, clear guidance, relevant examples, and continuous feedback. A total of 83% of responses fall into the very strong category, showing strong support for the use of instructional videos, online materials, and interactive classroom activities. The Flipped Classroom model is considered effective in promoting active learning and improving students’ paragraph writing skills.